Bronisław Łagowski o prawidłach polityki - Antipow, Emil (Czasopismo Prawno-Historyczne, 2018)
This paper presents the rules and principles which govern politics as depicted by Bronisław Łagowski, one of the most prominent Polish political philosophers. He constantly declares his position as a political realist and he interprets Polish political events from this point of view. The foundation of such an interpretation of politics is an anthropological assumption of human imperfection which is a crucial component of political realism as well as a great source of support for his opinions in history and in cultural achievements. The following principles were included among the presented rules of politics: the principle of protection of citizens by public authority, a restriction of will of the governing authorities by law, the so-called rule of expiration, an inability to justify some events after many years, the problem of social subjectivity, an inability to forgive on behalf of the whole nation, the problem of international claims as well as territorial changes after the Second World War. All of these elements were assumed as the basis of Polish politics.